An improvement sealing method for gas pressure measurement by drilling a reducing‐nipple borehole. Issue 5 (5th September 2018) - Wang, Long; Wang, Zhaofeng; Liu, Hai; Chen, Jinsheng; Yang, Tenglong
Abstract: Gas pressure measurement is one of the crucial steps for CBM resource extraction. However, the previous sealing methods are not applicable for horizontal boreholes owing to the autoshrinkage effect of cement mortar. The autoshrinkage tests of cement specimens with different water‐cement ratios were performed here, and then the gas flow model in an eccentric ring gap was established to analyze the autoshrinkage effect on the hole sealing. Furthermore, the selections of the initial sealing position and the grouting pressure were also discussed through the numerical method. The results show that the shrinkage amount would be decreased with the water‐cement ratio rising in the early setting stage, and the gas leakage amount of the eccentric model is larger than that of the concentric ring model. The initial sealing position should be kept away from the plastic zone around tunnel, which is related to the lithology of surrounding rock, the buried depth and the size of tunnel section. The diffusion radius of cement mortar would be enlarged with an increasing grouting pressure. While the grouting pressure reaching the threshold, the increment of diffusion radius would gradually descent. Eventually, a pressurized sealing method by drilling the reducing‐nipple borehole was successfully applied for the gas pressure measurement of the horizontal borehole in 7# coal seam, Liulong coal mine. Abstract : Gas pressure measurement is the crucial step for CBM resource extraction. However, the previous sealing methods are not applicable for horizontal boreholes owing to the autoshrinkage effect of cement mortar. We discussed the various influencing factors on the horizontal hole sealing, including the autoshrinkage effect of cement mortar on the gas leakage, the initial sealing position, and the grouting pressure. Finally, a pressurized sealing method by drilling a reducing‐nipple hole was successfully applied in the measurement test.